Síntese, caracterização e estudo teórico do cristal ternário de cobre (II) complexado com 1,10-fenantrolina e l-tirosina para o uso como antitumoral - PEREIRA, Walajhone Oliveira (2021)
Cancer is one of the main causes of death in the world, and in Brazil the estimative for new cases of the disease has increased considerably in recent years. Given this scenario, it is essential to search for new materials with antitumor properties that are more effective in combating this pathology and that minimize side effects during treatment. In this context, the objective this work was to synthesize the copper (II) ternary crystal complexed with 1,10- phenanthroline and L-tyrosine by the method of slow evaporation of the solvent, as well as to perform the theoretical study and of their physicochemical and biological properties aiming at its application as an antitumor agent. The crystal was obtained after a period of 30 days, being characterized by ultraviolet-visible (UV-Vis) absorption spectroscopy, X-ray diffraction (XRD) with Rietveld refinement, Fourier transform infrared (FT-IR) spectroscopy, Raman spectroscopy, differential scanning calorimetry (DSC), XRD as a function of temperature with Le Bail refinement, solubility test and evaluation of antitumor activity in vitro. Moreover, the computational study of the complex was performed using density functional theory (DFT). UV Vis spectroscopy showed that material crystallization occurs at acid pH of approximately 4. Through XRD at room temperature (300 K) it was verified that the crystal presents a monoclinic structure with spatial group P 21/c containing 4 molecules per unit cell and lattice parameters a = 9.385(2) Å, b = 25.458(3) Å, c = 10.942(2) Å and β = 120.08(1) °. Through the computational study it were obtained the optimized structure of the complex, the electrostatic potential map, the energies of the HOMO and LUMO orbitals, thermodynamic parameters and the chemical reactivity descriptors. FT-IR and Raman spectra showed the complexation of the Cu2+ metallic ion with the organic molecules, presenting their vibrational modes due to the molecular structure formed form tyrosine and phenanthroline with copper. Through the DSC it was verified that the ternary crystal presents thermal stability up to 321 K. The XRD as a function of temperature variation showed that the material undergoes a phase transformation by stabilizing into a new structure in temperature 354 K with monoclinic system, spatial group P 121 and lattice parameters a = 7.990(3) Å, b = 9.862(2) Å, c = 16.961(2) Å and β = 94.28(1) °. Furthermore, the crystal in 308 K presented good solubility profile compared to other drugs used in chemotherapy, reaching 48.16 mg/mL in 300 minutes. The antitumor activity of the complex was confirmed by in vitro cytotoxic tests on tumor cell lines of prostate cancer (PC3) and cancer of the central nervous system (SNB-19), presenting IC50 equal to 3.15 and 3.45 μM, respectively, more efficient than cisplatin and other compounds for theses strains. Therefore, the results obtained suggest that the copper (II) ternary crystal complexed with 1,10- phenanthroline and L-tyrosine presents antitumor activity, having potential to be used in the chemotherapy treatment of cancer cells.